1995
DOI: 10.1177/096120339500400208
|View full text |Cite
|
Sign up to set email alerts
|

Anti-beta 2-glycoprotein I antibodies: a marker of antiphospholipid syndrome?

Abstract: Anticardiolipin (aCL) and anti-beta 2-glycoprotein I(anti beta 2GPI) antibodies have been shown in animal models as not cross-reacting antibody populations. This observation prompted us to prove if anti-beta 2GPI exist in human sera by using a reliable method and then to investigate if these are independent from aCl antibodies. We have developed a new ELISA for the detection of anti-beta 2GPI antibodies employing the coating of the protein in carbonate buffer to irradiated microtitre plates and the filtration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
1
13

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 23 publications
5
91
1
13
Order By: Relevance
“…Our anti-2gp1 ELISA had comparable specificity to those included in the meta-analysis, despite the false positives noted in syphilis sera, which has been mentioned by other authors. 20 21 The sensitivity of our anti2gp1 assay was low compared with that of the pooled data, despite optimisation of antigen concentrations. Higher concentrations of 2gp1 do not necessarily improve sensitivity and have negative eVects on specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our anti-2gp1 ELISA had comparable specificity to those included in the meta-analysis, despite the false positives noted in syphilis sera, which has been mentioned by other authors. 20 21 The sensitivity of our anti2gp1 assay was low compared with that of the pooled data, despite optimisation of antigen concentrations. Higher concentrations of 2gp1 do not necessarily improve sensitivity and have negative eVects on specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Higher concentrations of 2gp1 do not necessarily improve sensitivity and have negative eVects on specificity. 20 The use of irradiated ELISA plates improves the detection of anti-2gp1 by inducing conformational changes in the antigen, 22 improved antigen binding, 23 or a combination of both. 11 (3) The studies discussed here may highlight genuine biological diVerences between patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antibodies reacting directly with p,GPI have been found. Both types of antibodies are thought to play a leading role in the pathogenesis of A P S since they closely correlate with the appearance of the typical clinical manifestations (15)(16)(17)(18)(19). Whether aPL-positive sera recognize epitopes displayed by P,GPI itself or whether the epitope consists of both P,GPI and cardiolipin (CL) is still open to discussion (20,21).…”
mentioning
confidence: 99%
“…$ Expressed as optical density values X 1,000; values higher than the 99th percentile in 164 normal human sera (130 for IgG and 280 for IgM) were regarded as positive (18).…”
mentioning
confidence: 99%
“…Guerin et al (62), however, failed to absorb the antibody reactivity in APS sera when using up to 640 g/ml of ␤ 2 GPI in solution. In contrast, many other authors have found that sufficiently high concentrations of ␤ 2 GPI (ϳ400 g/ml) in free solution significantly reduce aPL binding to ␤ 2 GPI on ELISA plates, in a dose-dependent manner (25,58,(63)(64)(65)(66)(67). The evidence that native ␤ 2 GPI may be recognized by aPL in Western blotting experiments is conflicting; some authors demonstrate binding (68,69), but others do not (62,70,71).…”
Section: Molecular Structure and Function Of ␤ 2 Gpimentioning
confidence: 93%